2017
DOI: 10.1111/ijn.12595
|View full text |Cite
|
Sign up to set email alerts
|

Clinically indicated replacement versus routine replacement of peripheral venous catheters in adults: A nonblinded, cluster‐randomized trial in China

Abstract: Clinically indicated PIVC replacement is feasible, and it may reduce nursing staff workload and patient discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 23 publications
(57 reference statements)
0
24
0
2
Order By: Relevance
“…Similarly, the current data demonstrate that the increasing dwell time of PVCs did not increase the frequency of phlebitis. 4,5,7,8,11 In a study conducted by Miliani et al, 12 a negative correlation was established between the dwell time of catheter and the risk of PVC-related complications. Another study showed that the risk of catheter failure may not remain constant throughout the dwell time, and the risk of PVC failure did not increase after the first 38 h. 13 A recent Cochrane review found no difference in phlebitis and infection risk between routine replacement and clinically indicated removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the current data demonstrate that the increasing dwell time of PVCs did not increase the frequency of phlebitis. 4,5,7,8,11 In a study conducted by Miliani et al, 12 a negative correlation was established between the dwell time of catheter and the risk of PVC-related complications. Another study showed that the risk of catheter failure may not remain constant throughout the dwell time, and the risk of PVC failure did not increase after the first 38 h. 13 A recent Cochrane review found no difference in phlebitis and infection risk between routine replacement and clinically indicated removal.…”
Section: Discussionmentioning
confidence: 99%
“…On the positive side, clinically indicated replacement of PVC can result in a longer dwell time without complication. 4 8 However, many risk factors related to the patient (e.g. age, immunodeficiency, diabetes mellitus, skin elasticity, vascular quality), the catheter (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan bukti penelitian yang ada, kebijakan saat ini untuk penggantian rutin 72-96 jam tidak efektif dan perlu dilakukan kebijakan penggantian IV karena indikasi klinis. Penelitian oleh Xu, Hu, Huang, Fu, & Zhang (2017), bahwa penggantian kateter IV dengan indikasi klinis dapat mengurangi ketidaknyamanan pasien. Dalam menerapkan penggantian IV karena indikasi klinis, ada hal penting yang harus yang dilakukan petugas yaitu memantau pemasangan IV secara teliti setiap hari untuk menilai tentang perlunya terapi IV dilanjutkan atau segera dilakukan penggantian/ pelepasan bila ditemukan indikasi klinis (Rickard, McCann, Munnings, & McGrail, 2010).…”
Section: Pembahasanunclassified
“…Salah satu kinerja yang dimaksud adalah mentaati SPO yang berlaku di rumah sakit. Salah satunya adalah SPO pergantian infus secara rutin setiap 3 hari, padahal pergantian dengan indikasi klinis lebih efektif dan efisien seperti yang dikemukakan oleh Xu et al, (2017), bahwa penggantian kateter IV dengan indikasi klinis dapat mengurangi beban kerja perawat. Selain itu menurut (Wu & Casella, 2013), bahwa pergantian selang intravena yang dilakukan secara klinis mengurangi beban kerja untuk staf klinis dan biaya perawatan kesehatan.…”
Section: Pembahasanunclassified
“…CF negatively affects the patient's comfort and continuous fluid therapy. Catheter replacement, which is unavoidable in CF, increases patient discomfort (8,9), labor costs, and the cost of medical resources (3,(10)(11)(12)(13)(14). For these reasons, it is important to prevent CF in PIVCs and to pay special attention to signs, symptoms, and changes in the infusion rate.…”
Section: Introductionmentioning
confidence: 99%